Kinetic Study of Electrochemical Treatment of Carbon Fiber Microelectrodes Leading to In Situ Enhancement of Vanadium Flow Battery Efficiency. Issue 9 (1st January 2016) - Miller, M. A.; Bourke, A.; Quill, N.; Wainright, J. S.; Lynch, R. P.; Buckley, D. N.; Savinell, R. F.
Abstract : Novel carbon fiber microelectrode (CFME) and flow cell experiments were used to investigate electrode treatments for vanadium flow batteries (VFBs). Linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) on CFMEs showed that electrode treatments at positive potentials enhance the kinetics of V 2+ /V 3+ and inhibit the kinetics of VO 2+ /VO2 +, while electrode treatments at negative potentials inhibit the kinetics of V 2+ /V 3+ and enhance the kinetics of VO 2+ /VO2 + . XPS analysis showed changes in oxygen-containing species on electrode surfaces after treatment, supporting the suggestion that such species are responsible for the observed effects. The kinetics of VO 2+ /VO2 + are significantly faster than that of V 2+ /V 3+ . Based on the CFME results, the range of potential experienced by a negative electrode in a flow cell during operation corresponds to a region where it is being deactivated by reduction, and the redox potential of the positive half-cell falls in a region where the electrode is activated for the V 2+ /V 3+ reaction. This is supported by flow cell experiments which showed that the overpotential at the negative electrode increases with charge-discharge cycling but decreases significantly when the positive and negative electrolytes are interchanged. Periodic electrolyte interchange and other in-situ electrochemical treatments of electrodes may be a practical means of improving voltage efficiency in VFBs.